PELATIHAN DAUR ULANG DALAM UPAYA MENGURANGI SAMPAH PLASTIK BAGI WARGA DESA KARANGGINTUNG, KABUPATEN BANYUMAS - Nuning Vita Hidayati; Hendrayana Hendrayana; Iqbal Ali Husni; Rizqi Rizaldi Hidayat; Aris Afandi; Dyahruri Sanjayasari; Riviani Riviani; Dewi Wisudyanti Budihastuti; Sesilia Rani Samudra; Nadhila Salwa Aisyah; Nuri Fitriya; Maria Dyah Nur Meinita (Universitas Mataram, 2023)
Plastic waste pollution has become one of the central issues of society in Indonesia, considering the various negative impacts on the environment, economy, safety, and health arising from the presence of this waste. Therefore, the Government of Indonesia has established policies to improve the performance of reducing household and household-like waste through various strategies. One of these strategies is the recycling and reuse of household waste and formal and informal education. This activity was carried out to provide education on the importance of protecting the environment and managing waste for the people of Karanggintung Village. In addition, providing training on making handicrafts made from plastic is an effort to manage waste. Activities are carried out with the stages of preparation for activities, counseling, implementation of training, and ending with activity evaluation. The training is carried out using the demonstration method carried out by a team of partners, lecturers, and students with a participatory approach that involves the community being actively involved in all activities. The activity was prepared by compiling an activity plan followed by coordinating with the Banyumas Regency Environmental Service (DLH) and the Karanggintung Village Head and his staff. After that, counseling was carried out about the importance of processing plastic waste to the public about the potential for plastic waste to enter the sea so that it is harmful to marine organisms. The next stage is training on processing plastic waste into various handicraft products, which is attended by community cadres who are expected to become a driving force for other communities. The training was carried out by demonstrating the manufacture of handicraft products made from plastic. After that, the participants practiced with the team. Handling plastic waste is very important to keep the environment clean. This can be done by recycling plastic waste into handicrafts.